The effect of herbage availability and species choice on grazing preference of dairy cattle : a thesis presented in partial fulfilment of the requirements for the degree of Masterate in Applied Science at Massey University - Torres-Rodríguez, Alberto (Massey University, 1997)
Herbage intake is one of the factors determining animal performance. Intake and quality of the diet consumed by animals are both determined by selective grazing. The motivation to graze selectively is in part a function of dietary preferences. The study of diet selection requires knowledge of what animals prefer to eat when there are no or minimal constraints to them obtaining their diet. This experiment aimed to investigate the effect of relative availability of a preferred species on dairy cattle response at grazing, and to evaluate the feasibility of the use of monocultures of pasture species for studies of preferences of dairy cattle. Three species-contrasts each composed of two adjacent 1-ha monocultures of either White clover:Ryegrass (W_Rye), Lotus corniculatus:Ryegrass (L_Rye) or Lotus corniculatus:Red clover (L_Red) were used. White clover (W) and lotus (L) had been previously determined as preferred over ryegrass (Rye) and red clover (Red). Each species-contrast was subdivided into four plots and the height of the preferred species was set at 4, 6, 8 and 10 cm, whereas that of the less preferred species was set at 10 cm across plots. Groups of yearling Holstein heifers grazed the plots, and observations on grazing behaviour were made by recording grazing activity and species location at 10-minute intervals during daylight hours for three consecutive days, twice in summer and twice in autumn during 95/96 at the AgResearch Flock House Research Centre, near Bulls. During summer, a second week of grazing followed each period of observations for grazing activity, where attempts to estimate herbage dry matter intake and diet composition using the alkane technique were made. From the species-location information, total grazing time (GTt), expressed in hours, and distribution of GTt between preferred (GTp) and less preferred (GTI) species was obtained. The proportion of GTt allocated to grazing the preferred species was considered as a measure of preference. Statistical analysis was performed by GLM procedures of SAS. Regression analyses were carried out for grazing activity parameters on actual height of the preferred species. Animals showed preference for a mixed diet with partial preference for the legume component (W, 67 %, and L, 70 %) over grass, whereas partial preference in the L_Red species-contrast was close to indifference (L, 55 %). However, this partial preference differed between seasons, being in general stronger in summer than in autumn. Partial preference decreased with decreases in height of the preferred species. However, herbage bulk density (BD) appeared to be important also in influencing preference since more marked responses to height were observed in autumn when sward had lower BD compared with summer. Botanical composition of the sward upper stratum was also considered to influence animal preferences. Diet composition estimation from herbage and faecal alkanes suggested that animals consumed the preferred species at higher proportions than indicated by the proportion of GTt allocated to the preferred species. This was possibly due to differences in rate of intake between herbage species. However, more research is needed in this area in order to establish more accurately the relationship between these two techniques. It is concluded that animals respond to changes in herbage availability of a preferred species and to species choice by adjusting grazing time between preferred and less preferred species. It would be appropriate to research the potential animal performance benefits of increasing the availability of a preferred species in proportion to that preferred by the animals. This works confirms the use of monocultures of pasture species to be useful in the evaluation of preference of dairy cattle. Inclusion of a wider arrangement of species-contrasts is recommended.
Keywords: Dairy cattle feed; Dairy cattle grazing; Pasture